Efficacy Verification of Team Learning Satisfaction, Problem Solving Ability, and Communication Ability of Problem Solving Process Classes Applying Action Learning, Problem-Based Learning, and Mentoring - Hwang-Woo Byun (Halla Newcastle Education and Research Center, 2020)
The purpose of this study was i) to design a teaching and learning model for problem solving ability class to which action learning (AL), problem-based learning (PBL), and Mentoring are applied, ii) implement the model to verify the effects of AL's on team learning, iii) analyze the enhancement of problem solving ability through PBL and iv) review development of communication skills through mentoring. The effect of team learning, improvement of problem solving ability within PBL, and improvement in communication through mentoring was verified through comparison of results from quantitative pre- and post-tests. Data was collected two times in the form of a questionnaire for 62 students at the beginning and at the end of the first semester of 2020. A paired samples t-test was among the methods of average comparison on the SPSS 18.0, used to determine differences in team learning satisfaction, problem solving ability, and communication skills based on experiences in AL, PBL, and Mentoring. The results of the test verified the efficacy of PSP class to which AL, PBL, and Mentoring were applied.